Digital Transformation of Halal Food MSMEs to Increase Competitiveness: A Qualitative Case Study of Makcik Cam Traditional Culinary in Medan - Khairiah, Dian; Bi Rahmani, Nur Ahmadi; Imsar (Universitas Islam Negeri Alauddin Makassar, 2025)
Digital transformation has become a key element in increasing the competitiveness of micro, small, and medium enterprises (MSMEs), especially in the halal culinary sector, which faces challenges adapting to technology and digital market dynamics. This study aims to analyze the implementation of digital transformation in the Makcik Cam MSME, to understand its impact on increasing competitiveness and the strategies implemented in facing the challenges of digitalization. Using a qualitative approach with a strategic case study on the Digital Transformation of Halal Food, data was collected through observation, in-depth interviews, and documentation of the business. This study used inductive thematic analysis. The results show that the digitalization process is carried out gradually through the use of social media, online platforms, and social network-based promotions. However, limited digital literacy, technological infrastructure, and marketing data management are key challenges. This research demonstrates that halal values ​​are appropriate because they ensure that the entire production, distribution, and marketing processes of a product or service meet halal standards established by Islamic law and provide added value to consumers and businesses. This study provides theoretical contributions in developing the concept of locally-based digital transformation and halal values, and offers effectiveness for halal culinary MSMEs in Indonesia.